2008
DOI: 10.2754/avb200877010081
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Responses of Trigonal Smooth Muscle from Rabbit by Alpha1-Adrenoceptor Antagonists Alfuzosin, Doxazosin and Tamsulosin

Abstract: This study was performed to investigate the effects of alfuzosin, doxazosin and tamsulosin in vitro on trigone smooth muscle of rabbit. In this study, fifteen rabbits weighing 2.5 -3 kg were used. One strip in the shape of a trigone was prepared for each of the isolated bladders. Firstly, an initial tension of 1 g was placed on each segment, and we waited for equilibration by constantly bubbling with 95% O 2 and 5% CO 2 . Next, the determination level of electrical stimulation which created submaximal contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Exposure of liver to some chemicals or drugs leads to morphological changes and in turn affects homeostatic balance of many processes (Arika et al, 2016). Drug induced hepatic injury have become a major hurdle to pharmaceutical industry leading drug development termination, post-market withdrawal and many more (Karadeniz et al, 2008;Sharif et al, 2013;Abubakar et al, 2015;Arika et al, 2016;Odusanya et al, 2017;Enroth et al, 2018;Kaplan, 2019).…”
Section: Histopathology Analysis Of and Livers At 6 Th And 8 Th Weeksmentioning
confidence: 99%
“…Exposure of liver to some chemicals or drugs leads to morphological changes and in turn affects homeostatic balance of many processes (Arika et al, 2016). Drug induced hepatic injury have become a major hurdle to pharmaceutical industry leading drug development termination, post-market withdrawal and many more (Karadeniz et al, 2008;Sharif et al, 2013;Abubakar et al, 2015;Arika et al, 2016;Odusanya et al, 2017;Enroth et al, 2018;Kaplan, 2019).…”
Section: Histopathology Analysis Of and Livers At 6 Th And 8 Th Weeksmentioning
confidence: 99%
“…Some researchers showed that the in vivo contractions of dog [19], and invitro contraction of rat [20], the smooth muscle of prostate induced by epinephrine and phenylephrine are inhibited by tamsulosin. Moreover, the contractions resulted by phenylephrine in the human prostate smooth muscle are blocked by increasing the concentration of tamsulosin, others mentioned that the contractions by phenylephrine in the dog bladder prevented by tamsulosin competitively [21].…”
Section: The Vasorelaxant Effect Of Tamsulosin On Isolated Renal Artementioning
confidence: 99%
“…Also Troxel, et al [22], found that the addition of tamsulosin blocks the stimulatory effect of phenylephrine. Previously mentioned that, contractions of the rat tail [23], and mesenteric artery [24], induced by phenylephrine or noradrenalin were semi completely prevented by tamsulosin as compared to the effects of other alpha-adrenergic antagonists, such as prazosin, phentolamine, and tamsulosin hydrochloride may cause facilitate flow of urine by inhibition of alpha-adrenergic receptors in diverse species [21]. The result of the current study regarding the renal artery supports the previous findings for the contraction inhibitory of tamsulosin in other tissues; this may be due to the presence of the receptors in the renal artery.…”
Section: The Vasorelaxant Effect Of Tamsulosin On Isolated Renal Artementioning
confidence: 99%
“…Multiples studies prove that a adrenoreceptors blocker plays an important role in treating acute urinary retention in case of benign prostatic hyperplasia (BPH) [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%